2019
DOI: 10.1158/1538-7445.sabcs18-pd2-05
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD2-05: Biomarker analysis by baseline circulating tumor DNA alterations in the MONALEESA-3 study

Abstract: Background: In the Phase III MONALEESA-3 (NCT02422615) study, ribociclib (RIB; cyclin-dependent kinase 4/6 inhibitor) + fulvestrant (FUL) significantly prolonged progression-free survival (PFS) vs placebo (PBO) + FUL in postmenopausal women with hormone receptor-positive (HR+), HER2-negative (HER2–) advanced breast cancer (ABC). Here we present MONALEESA-3 efficacy data by molecular alterations detected in circulating tumor DNA (ctDNA) at baseline. Methods: Postmenopausal women (N=726) with HR+,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…Contrastingly, PIK3CA mutations were detected in the circulating DNA of 129 patients enrolled in PALOMA-3, with no significant association observed with response to treatment (9). Similarly, biomarker analysis of MONALEESA-3 demonstrated consistent benefit from ribociclib plus fulvestrant, irrespective of PIK3CA alteration status, as detected in baseline circulating tumor DNA (35). Functioning downstream of PI3K is 3-phosphoinositide-dependent protein kinase 1 (PDK1), a vital requisite for the full activation of AKT (36).…”
Section: Mechanisms Of Resistance—avenues For Possible Molecular Biommentioning
confidence: 93%
“…Contrastingly, PIK3CA mutations were detected in the circulating DNA of 129 patients enrolled in PALOMA-3, with no significant association observed with response to treatment (9). Similarly, biomarker analysis of MONALEESA-3 demonstrated consistent benefit from ribociclib plus fulvestrant, irrespective of PIK3CA alteration status, as detected in baseline circulating tumor DNA (35). Functioning downstream of PI3K is 3-phosphoinositide-dependent protein kinase 1 (PDK1), a vital requisite for the full activation of AKT (36).…”
Section: Mechanisms Of Resistance—avenues For Possible Molecular Biommentioning
confidence: 93%
“…In these analyses, treatment with fulvestrant (including in combination with a CDK4/6i) showed potential efficacy benefit in patients with ESR1-mutated tumors. [36][37][38] Fulvestrant, rather than EXE (which was used in TRINITI-1), may be a more suitable option for these patients; however, it is unknown whether continuation of a CDK4/6i in combination with fulvestrant and EVE would be the optimal treatment. Consistent with the results of TRINITI-1, PIK3CA was the most common mutation in BOLERO-2 and the median PFS was shorter in patients with mutated PIK3CA.…”
Section: Safetymentioning
confidence: 99%
“…This polytherapy improved PFS regardless of ctDNA genetic alterations at baseline: PIK3CA, TP53, CDH1, FGFR1, cell cycle-related genes or genes involved in receptor tyrosine kinase signalling [54]. However, Neven et al found shorter PFS was correlated with altered gene status irrespective of treatment (polytherapy or letrozole alone) [54], [55].…”
Section: Circulating Tumour Dna (Ctdna) Analysis As a Promising Tumour Biomarkermentioning
confidence: 97%